Plasma Heat Shock Protein 70 Is Associated With the Onset of Acute Myocardial Infarction and Total Occlusion in Target Vessels - Wu, Runda; Gao, Wei; Dong, Zheng; Su, Ya; Ji, Yuyao; Liao, Jianquan; Ma, Yuanji; Dai, Yuxiang; Yao, Kang; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
Background: Whether the role of plasma heat shock protein 70 (HSP70) in acute myocardial infarction (AMI) is protective or detrimental remains debated, and the relationship between HSP70 and total occlusion remains elusive. Methods: A total of 112 patients with primary diagnosis of AMI and 52 patients with chronic coronary syndrome (CCS) were enrolled into the study. Plasma HSP70 level was determined by ELISA on day 1 and day 7 post the onset of AMI, and was examined before angiography in patients with CCS. Peak NT-proBNP, high-sensitivity C-reactive protein (CRP), troponin T (cTnT), and left ventricular ejection fraction were measured. Results: Plasma HSP70 was significantly higher in CCS than AMI (P<0.0001), and it showed a significant decrease from day 1 to day 7 after AMI (P<0.01). Elevated HSP70 was associated with decreased levels of LDL-C (P<0.05), peak cTnT (R=-0.3578, P<0.0001), peak NT-proBNP (R=-0.3583, P<0.0001), peak CRP(R=-0.3539, P<0.0001), and lower diagnosis of AMI (R=-0.4016, P<0.0001) and STEMI (R=-0.3675, P<0.0001), but a higher diagnosis of total occlusion in target vessels (R=0.1702, P<0.05). HSP70 may provide certain predicative value for the diagnosis of AMI, STEMI and total occlusion in target vessels, and the area under the receiver operating characteristic curves were 0.7660, 0.7152, and 0.5984, respectively. HSP70 was also negatively associated with in-hospital stay (P<0.001) and positively correlated with left ventricular ejection fraction (LVEF) at one-year follow up (P<0.05), despite no association with in-hospital major adverse cardiovascular events (MACE). Conclusion: Plasma HSP70 level was found to decrease from day 1 to day 7 post AMI, but the overall level of patients with AMI was lower than CCS. However, the ability of HSP70 to identify clinically significant AMI and STEMI was moderate, and the predictive value to total occlusion was slight.